Touchdown Enzyme Time Release-PCR for Detection and Identification of Chlamydia trachomatis, C. pneumoniae, and C. psittaci Using the 16S and 16S-23S Spacer rRNA Genes - Madico, Guillermo (American Society for Microbiology, 2000)
Three touchdown enzyme time release (TETR)-PCR assays were used to amplify different DNA sequences in the variable regions of the 16S and 16S-23S spacer rRNA genes specific for Chlamydia trachomatis, Chlamydia pneumoniae, and Chlamydia psittaci as improved tests for sensitive diagnosis and rapid species differentiation. The TETR-PCR protocol used 60 cycles of amplification, which provided improved analytical sensitivity (0.004 to 0.063 inclusion-forming unit of Chlamydia species per PCR). The sensitivity of TETR-PCR with primer set CTR 70-CTR 71 was 96.7%, and the specificity was 99.6%, compared to those of the AMPLICOR PCR for the detection of C. trachomatis in vaginal swab samples. TETR-PCR for C. pneumoniae with primer set CPN 90-CPN 91 was 90% sensitive and 93.3% specific compared with a nested PCR with primer set CP1/2-CPC/D for clinical respiratory samples. TETR-PCR for C. psittaci with primer set CPS 100-CPS 101 showed substantial agreement with cell culturing (κ, 0.78) for animal tissue samples. Primer sets were then combined into a single multiplex TETR-PCR test. The respective 315-, 195-, and 111-bp DNA target products were precisely amplified when DNA from each of the respective Chlamydia species or combinations of them was used. Multiplex chlamydia TETR-PCR correctly identified one strain of each of the 15 serovars of C. trachomatis, 22 isolates of C. pneumoniae, and 20 isolates of C. psittaci. The primer sets were specific for each species. No target products were amplified when DNA from C. pecorum or a variety of other microorganisms was tested for specificity. TETR-PCR with primers selected for specific sequences in the 16S and 16S-23S spacer rRNA genes is a valuable test that could be used either with individual primers or in a multiplex assay for the identification and differentiation of Chlamydia species from culture isolates or for the detection of chlamydiae in clinical samples.